Phytochemical compounds extraction from medicinal plants by subcritical water and its encapsulation via electrospraying - Siti Machmudah (Elsevier, 2022)
In this study, phytochemical compounds were extracted and encapsulated from medicinal plants such as M. oleifera, S. androgynus, and S. grandiflora using subcritical water and the electrospraying technique. The extraction was conducted at temperatures of 120 to 160 °C at various extraction pressures from 1 to 10 MPa in semi-batch systems with a 1.0 mL min−1 flow rate. Under these conditions, the starting materials, that is the medicinal plants, underwent thermal cleavage, allowing the removal of their components. The Fourier transform infrared spectroscopy (FT-IR) spectra of the solid residues indicated that phytochemical compounds were successfully extracted from these medicinal plants. The results revealed that the amounts of extracted phenolic compounds did not increase linearly with increasing extraction temperatures and pressures. The amounts of extracted phenolic compounds could approach 82.26 (140 °C, 5 MPa), 75.32 (160 °C, 5 MPa), and 78.91 (160 °C, 10 MPa) mg of gallic acid equivalents (GAE)/g of dried samples for M. oleifera, S. androgynus, and S. grandiflora, respectively. When the extracted phytochemical compounds were encapsulated with polyvinylpyrrolidone (PVP) via the electrospraying technique, the particle products seemed to exhibit spherical morphologies with diameters less than 1 μm, and the FT-IR spectra of these particle products showed that the medicinal plant extracts were successfully encapsulated by PVP through this technique.